Mother’s perceptions of healthy diet for children in Ukraine - Lesia Heiko; Tetiana Yurochko (Health Economics and Management Review)
Multiple chronic diseases could be prevented by introducing and implementing healthy diet policies oriented for preschool children in the time of setting life-long habits. The role of mothers is highlighted to be crucial for a preschooler’s diet. It was important to conduct research to explore and investigate mothers’ perceptions of healthy diet for children in small towns in Ukraine. The study applies the qualitative methodology of semi-structured interviews using the strategy of a snowball and maximum variation sampling approaches interviewing mothers of preschool children in Lubny (Poltava Region, Ukraine) including local- and national-level health experts. As the research instrument, a topic guide was developed. It is based on the categories of analysis. The study displays that there is a variety of perceptions around healthy diet among interviewed mothers and health experts. It was also confirmed by previous studies that the mothers’ perceptions of a healthy diet for children are highly linked to socio-demographic characteristics which was found in the article. Common for all interviewed mothers was the perception about fresh fruits and vegetables consumption as the additional component of the child’s diet, but not the basis. None of the mothers was fully aware of World Health Organisation recommendations for a healthy diet. Based on the results, we conclude that mothers of preschool children in Lubny may be grouped into three main types by their perceptions about healthy diet: 1) the conservative type (mothers who prefer traditional meals for children and have a high level of trust to medical doctors and institutions in Lubny); 2) the loyal type (mothers have the same perceptions about healthy diet as conservative yet with a high loyalty to junk food in children’s diet); 3) the critical type (mothers who reported different from conservative type perceptions about healthy diet and tend to have low level of trust to the medical doctors and institutions in Lubny). The study represents findings relevant for Lubny and Poltava Region in Ukraine. Further research is needed to provide more data for a better understanding of perceptions about a healthy diet for children in Ukraine.